PROFIL GENETIK DAN PETERNAK SAPI PERANAKAN ONGOLE SEBAGAI STRATEGI DASAR PENGEMBANGAN DESA PUSAT BIBIT TERNAK - Nonok Supartini; Hariadi Darmawan (BUANA SAINS, 2014)
The aims of this study was to evaluaste genetic profiel, farmer’s cow PO and factor-factor to support development of cow PO. The study was conducted at Napis village, sub district Tambakrejo and district Bojonegoro in September 2012. Research material was PO cow age before 1 week and choose by simple random sampling. Study metodology was survey and the location was decided by purpose sampling. Data collection consist of body weight, value statictical vital, characteristic, silsilah, heratability value and breeding value. Primier data collected from interview to repondent and dokumentation, while secondary data base on supporting data and link office. The study result showed that profiel of PO cow have high value of body weight was from bull no 6 (belong to Kasiman in sub district Kalidandang) with heritability value 78%. Profil of farmer’s cow owner about 2,1 each or as same as 1,84 UT each household. Management by farmer is very simple and traditonal. Basic education is fundamental school (48,36%) with age of 45-55 (36.0%) and final desecion done by compromise (72,95%). The main factor for suporting development of PO for the centre of cow was society and enviromental condition (cow and natural resources)